2023
DOI: 10.1039/d2rp00140c
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of success in organic chemistry based on a mathematics skills test and academic achievement

Abstract: Organic Chemistry I presents challenges to many students pursuing diverse fields of study, oftentimes curtailing further progress in those fields. The ability to identify students at risk of unsuccessful course...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…In addition to the publication on Chem 1 students, the team published another study on Chem 2 students with even higher predictability identifying 83% of the successful students. In an organic chemistry student study, the evaluated data included student's MUST score, their first-exam score, and their prior GPA, which improved predictability to about 90% (Lee, Rix & Spivey, 2022). Results from all these studies support that students who enter with higher MUST scores statistically outperform the others as indicated by their end-of-course averages.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the publication on Chem 1 students, the team published another study on Chem 2 students with even higher predictability identifying 83% of the successful students. In an organic chemistry student study, the evaluated data included student's MUST score, their first-exam score, and their prior GPA, which improved predictability to about 90% (Lee, Rix & Spivey, 2022). Results from all these studies support that students who enter with higher MUST scores statistically outperform the others as indicated by their end-of-course averages.…”
Section: Instrumentmentioning
confidence: 99%
“…First-semester organic chemistry (O-Chem I) NSA team studies have also revealed that the mental skills required for successful completion of general chemistry may be similar to those required for success in O-Chem I (Bodenstedt et al, 2022;Lee, Rix, & Spivey, 2022); students who understand the procedures needed to solve these arithmetic problems may also find noted chemical reactions and mechanisms easier to comprehend and retain.…”
Section: Instrumentmentioning
confidence: 99%
“…These characteristics, which contribute to high general chemistry grades as well as to organic chemistry success, likely include a mixture of domain knowledge, cognitive skills, and study habits. Some researchers have studied the impact of specific cognitive skills, such as problem solving ability, spatial visualization ability, or math ability . Others have studied attitude characteristics, such as self-reported interest, confidence, and enthusiasm .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have studied the impact of specific cognitive skills, such as problem solving ability, 4 spatial visualization ability, 5 or math ability. 6 Others have studied attitude characteristics, such as self-reported interest, con-fidence, and enthusiasm. 7 Others have studied social characteristics, such as being a first-generation college student.…”
Section: ■ Introductionmentioning
confidence: 99%